Body Composition Status of a Physically Independent 86-Year-Old Man: A Case Report - Moris, Jose M; Curtis, Ryan; Fitzgibbons, Abigail; Burnam, Britney; Koh, Yunsuk (Journal of Sports Research, 2022)
A physically active lifestyle is known to be beneficial for optimal aging. However, as people get older, sedentary lifestyles become more prominent, especially in populations over the age of 80. The increase in sedentary behaviors can make the studying of geriatric populations challenging and limiting. Thereof, this descriptive study presents the case report of an 86-year-old man who has been physically active for over a decade. This study highlights the utilization of a dual-energy X-ray absorptiometry scan to assess the body composition of the participant, along with a qualitative interview to examine the lifestyle of the participant. Overall, the participant presented an optimal amount of body fat percentage and bone mineral density. In addition, the participant reported having a satisfactory quality of life, which are benefits linked to the participant remaining physically active after major surgical procedures. Altogether, this study denotes the importance of physical activity for healthy aging.